REPRESENTATIF SAHABAT MENYENANGKAN DALAM TVC OREO SEBAGAI MARKETING COMMUNICATION STRATEGY - Lim Yudhi (Universitas Bunda Mulia, 2015)
In mid August 2015, the world was hit by an advertisement that is unique in terms of the song until the very interesting visualization. Oreo miraculous fever hit several countries. Oreo ad that aired in several countries accompanied by the translation of the lyrics of the songs contained in the Oreo ad. Selection of the characters used in the ad interesting. One of the countries that serve such ads is Indonesia. In Indonesia, Oreo ads with the theme of